Second Language Writing Instruction: Teaching Writing to English Language Learners - Kanakri, Aseel (Widya Mandala Catholic University Surabaya, 2016)
This article discusses the academic writing challenges and needs of English as second language (ESL) students. Specifically, it aims at in-depth understanding of the needs of ESL students in academic environments with regards to academic writing across the disciplines. It also elaborates on the role of genre study (theory) in helping ESL students overcome their challenges and meet the requirements of their academic disciplines. This article calls for the importance of understanding ESL student’ needs and challenges which can help in developing better instruction, dictate the curriculum, and provide a systematic support for these students to succeed and complete their degrees.